2019
DOI: 10.1002/jhet.3549
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Molecular Docking, and Anticancer Evaluation of 4‐Thiazolidinone Analogues

Abstract: Scaffolds containing one or more heteroatoms are ubiquitous in nature and are responsible for almost every biological processes in flora and fauna. The fact that heterocyclic cores have high propensity for biological targets, several nitrogen, oxygen, and sulfur‐containing heterocyclic compounds have been reported in the last few decades. One such intriguing class is 4‐thiazolidinone that exhibit diverse range of pharmacological activities. In the present study, we report synthesis, characterization, molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
(152 reference statements)
1
5
0
Order By: Relevance
“…Our results agreed with previous work (Aly et al, 2020; Ding & Nguyen, 2013; Havrylyuk et al, 2012; Mushtaque et al, 2019; Sonego et al, 2020; Yurttaş & Çiftçi, 2018) of the reported history of the tested derivative of quinoline or thiazolidinone‐based derivatives as apoptosis‐inducing agents.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agreed with previous work (Aly et al, 2020; Ding & Nguyen, 2013; Havrylyuk et al, 2012; Mushtaque et al, 2019; Sonego et al, 2020; Yurttaş & Çiftçi, 2018) of the reported history of the tested derivative of quinoline or thiazolidinone‐based derivatives as apoptosis‐inducing agents.…”
Section: Resultssupporting
confidence: 93%
“…Over the years, many quinoline derivatives have been synthesized and reported for anticancer activity (Afzal et al, 2015; Gopaul et al, 2015; Mohamed & Abuo‐Rahma, 2020; Solomon & Lee, 2011). It has also been well established that thiazolidines are incorporated in the structure of many promising anticancer compounds (Abumelha & Saeed, 2020; Deep et al, 2016; Havrylyuk et al, 2012; Irfan et al, 2020; Mushtaque et al, 2019; Nirwan et al, 2019; Türe et al, 2020). Quinoline derivatives act actively as anticancer agents through several mechanisms such as interfering with cell migration, growth inhibition, apoptosis induction, and cytotoxicity through DNA intercalation (Jain et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In [ 49 ], the synthesis and study of molecules 48 and 49 ( Figure 20 ), as modified analogues of hybrids 46 and 47, was reported. The authors applied the bioisosteric replacement of the pyridine core by the substituted benzene ring for the design of novel target molecules with desirable anticancer properties.…”
Section: Privileged Heterocyclic Scaffolds–4-thiazolidinones Hybrid M...mentioning
confidence: 99%
“…[11] Thiazolidin-4-one and its derivatives have a wide range of pharmacological activities such as anticancer [12][13][14][15][16][17] anti-inflammatory, analgesic, anticonvulsant, antimicrobial, local and spinal anesthetics, central nervous system stimulants, hypnotics, anti-HIV, antidiabetic, follicle-stimulating hormone receptor antagonist. [18][19][20][21][22] The aim of this study is to develop new and effective anticancer agents through the synthesis of thiazolidin-4-one derivatives of 4-furfuryloxy-benzohydrazide. To achieve this, 16 new compounds were synthesized and their cytotoxic effects were tested in vitro against both MCF7 human breast cancer cells and MCF10A human healthy breast tissue.…”
Section: Introductionmentioning
confidence: 99%